PENGALAMAN PEREMPUAN INFERTIL DALAM MENCARI PENGOBATAN DI YOGYAKARTA - LUBIS, DINA PUTRI UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Introduction: The fertile spouse's age in Indonesia about 10-15% of couples having fertility problems. In Yogyakarta has society patriarchal culture that embraces husband as decision makers and their terms about koncowingking where women as subordinated.Based on the theory of Health Promotion Model, taking action for recovery and improvement of the quality of life of women in this search experience in overcoming infertility treatment. Aim: To explore about the meaning and significance of infertile women's life experiences in seeking treatment. Method: This research used qualitative design research with phenomenology approach. Research was carried out in June to August 2014 in public hospitals PKU Muhammadiyah Yogyakarta. The informant were four women who have never pregnant. Instrument in this research is researcher, guidelines with uses in-depth interviews, field notes and recorder. Data analysis used steps of Colaizzi. Results: The research found seven themes in the study of variations in the treatment of the various obstacles that, in our experience, the sources in the treatment decision, discomfort in undergoing treatment, the support received during the treatment, the problem of self-infertile women, and the concept of the strategy selected koping. Discussion: The experience of infertile woman in search for a variety medical treatment and the alternative, then there are obstacles in the form of the husband does not allow, disappointed treatment often fails and the high cost of treatment. Sources of support obtained from husbands of infertile women, friends and those who are experienced . There is discomfort in the form of physical and psychological effects and grieving response to coping strategies to perform prayers and alms.